Predictors for Post Transplant Survival in Patients with Acute-on-Chronic Liver Failure. (July 2018) - Sterneck, Martina; Huebener, Peter; Bangert, Katrin; Drolz, Andreas; Kluge, Stefan; Lohse, Ansgar; Fischer, Lutz; Fuhrmann, Valentin
Abstract : Background: Acute-on-chronic liver failure (ACLF) is a severe complication of liver cirrhosis associated with excess short-term mortality rates. Orthotopic liver transplantation (OLT) is a potentially life-saving therapeutic modality for ACLF patients, but selection of transplant candidates with an acceptable post-OLT outcome is difficult. Objective: The aim of this study was to assess the risk of OLT in patients with ACLF, and to determine parameters that predict post-OLT survival in this patient cohort. Methods: We retrospectively analyzed all patients with liver cirrhosis who underwent their first liver transplantation at the University Hospital Hamburg Eppendorf between 2009 and 2014 and assessed risk factors for post-transplant outcomes. Results: Of 250 cirrhotic liver transplant recipients, 98 patients fulfilled the diagnostic criteria for ACLF in the 3-month pre-transplant period. Compared to non-ACLF patients, ACLF was associated with significantly higher short-term morbidity and mortality after OLT (90-day patient survival: non-ACLF 96.1% versus ACLF patients 72.4%, p<0.0001). Clinical improvement in the pre-transplant period, as defined by recovery of at least one previously failed organ system, was observed in 37 of 98 (40%) ACLF patients, mostly within several days after diagnosis. In the multivariate analysis clinical improvement prior to OLT was the strongest predictor for post-transplant survival. In patients improving prior to transplantation post-transplant outcome was similar to non-ACLF OLT recipients. Following the 90-day post-transplant period, patient survival and long-term graft functions were comparable between ACLF and non-ACLF OLT recipients for up to five years. Conclusion: Given the dismal prognosis of ACLF, our results indicate that ACLF patients can be transplanted with comparably good outcomes, in particular patients who improve under conservative therapeutic measures.. Figure. No caption available.